Delusional disorder: no gender differences in age at onset, suicidal ideation, or suicidal behavior - González-Rodríguez,Alexandre (2014)
Objective: To investigate gender differences in age at onset, psychopathology, and suicidal behavior rates in delusional disorder (DD). Methods: We conducted a prospective longitudinal study of 97 patients with DD. Demographic and clinical data at baseline were recorded. Gender differences were investigated by applying analysis of covariance, using age at onset and age at first psychiatric consultation as dependent variables, comorbid depression and gender as between-subject factors, and employment status, social support, and DD types as covariates. Results: Seventy-six percent of the patients were women. The average age at onset was 48.76±12.67 years, mean age at first psychiatric consultation was 54.13±13.67 years, and men were more likely to be employed than women (p = 0.041). Despite the earlier age at onset and at first psychiatric consultation in men, these differences tended to disappear when adjusted for potential confounders. There were no significant gender differences in depressive comorbidity, presence of suicidal ideation and behavior, or compliance rates at follow-up. Conclusions: Our findings could not confirm that male and female DD patients differ in age at onset, age at first psychiatric consultation, or suicidal ideation and behavior, even after controlling for potential confounders.